Solutions: x=1<span>. Hope its right :)</span>
Answer:
false is the correct answer of it if the answer going wrong sorry
Answer:
1
Step-by-step explanation:
![(3^{n-1})\cdot(3^{1-n})\\\\=3^{n-1+1-n}\\\\\longrightarrow n-1+1-n=(n-n)+(-1+1)=0+0=0\\\\=3^{0}\\\\=1](https://tex.z-dn.net/?f=%283%5E%7Bn-1%7D%29%5Ccdot%283%5E%7B1-n%7D%29%5C%5C%5C%5C%3D3%5E%7Bn-1%2B1-n%7D%5C%5C%5C%5C%5Clongrightarrow%20n-1%2B1-n%3D%28n-n%29%2B%28-1%2B1%29%3D0%2B0%3D0%5C%5C%5C%5C%3D3%5E%7B0%7D%5C%5C%5C%5C%3D1)
Answer:
$1.46
Step-by-step explanation:
Required cards for winning :
1's, 2's and 3's
There are 4 cards of each in a total of 52 cards ;
Therefore, number of winning cards ;
(4 * 3) = 12 cards
Hence,
P(winning) = 12 / 52 = 3 / 13
P(not winning) = 1 - 3 /13 = (13 - 3) / 13 = 10/13
Earning (X)
Amount earned for winning = $43
Amount lost for not winning = $11
X ___ $43 ______ - $11
P(X) _ 3/13 _______ 10/13
Expected value, E(X) = ΣX*P(X)
Σ(X) = (43 * 3/13) + (-11 * 10/13)
E(X) = 9.9230769 - 8.4615384
E(X) = 1.4615385
E(X) = $1.46
Answer:
x = - 8
Step-by-step explanation:
4x - 9 + 3x = 8x - 1
7x - 9 = 8x - 1
7x - 8x - 9 = 8x - 8x - 1
- x - 9 = - 1
- x - 9 + 9 = - 1 + 9
- x = 8
- x ÷ - 1 = 8 ÷ - 1
x = - 8